KEEFEKTIFAN MODEL PEMBELAJARAN THINK PAIR AND SHARE DALAM MATA PELAJARAN EKONOMI PADA SMAN 3 BANDA ACEH - Faridah Yahya (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
This writing is intended to know 1) teachers’ ability in using Think Pair and Share learning type on economic accounting. 2) students’ response in the learning type. 3) students’ learning completion after Think Pair and Share learning type is applied. This research sample was students grade XI IPS 1 that amounted to 32 students. The technique of collecting data in this research including observation, questionnaires and test. Data analysis using percentage formula. The research’s result showed that teachers’ ability in accomplishing Think Pair and Share learning type on economic accounting material included good with total average 3.8. while students’ response towards the learning by use of think pair and share learning type in economic accounting material is happily 96. 87%, very willingly as much as 90. 63%. Furthermore, students’ learning completion by using think pair and share learning type gained a classical score as much as 81. 25%.  Keyword: think pair and share learning type, learning completion.